2007
DOI: 10.1093/eurheartj/ehm212
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic estimates of myocardium at risk during acute myocardial infarction: validation study using cardiac magnetic resonance imaging

Abstract: The myocardium at risk of infarction can be determined angiographically as validated in subjects with transmural myocardial infarcts. Salvage provided by early reperfusion or collaterals occurs by limiting infarct transmurality, thereby the extent of endocardial infarct involved also allows estimation of the myocardium at risk in patients presenting with STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 21 publications
3
105
2
1
Order By: Relevance
“…¶ The area at risk was assessed by means of the Alberta Provincial Project for Outcome Assessment in Coronary Heart Disease (APPROACH) score. 16 The APPROACH score is a scoring system in which the left ventricle is divided into regions defined by the distribution of perfusion of each coronary artery, and the estimated amount of myocardium in each region is used to calculate the amount of jeopardized myocardium for a given site of vessel occlusion. The area at risk is expressed as the percent of the left ventricular mass.…”
Section: Discussionmentioning
confidence: 99%
“…¶ The area at risk was assessed by means of the Alberta Provincial Project for Outcome Assessment in Coronary Heart Disease (APPROACH) score. 16 The APPROACH score is a scoring system in which the left ventricle is divided into regions defined by the distribution of perfusion of each coronary artery, and the estimated amount of myocardium in each region is used to calculate the amount of jeopardized myocardium for a given site of vessel occlusion. The area at risk is expressed as the percent of the left ventricular mass.…”
Section: Discussionmentioning
confidence: 99%
“…The angiograms were analyzed for collateral flow to the infarct-related artery according to the Rentrop classification grade (0-3), TIMI flow grade (0-3), and for area at risk according to the APPROACH (Alberta Provincial Project for Outcome Assessment in Coronary Heart Disease) score (34).…”
Section: Angiographymentioning
confidence: 99%
“…84 Taking these aspects into account, Ortiz-Perez et al showed that CMR infarct endocardial surface area (ESA) measured within a week after primary PCI in STEMI patients correlated with the angiographically determined AAR. 18 The use of T 2 -weighted images in determining the AAR has its limitations. 85 In a review article, Arai et al discussed the role of T 2 -weighted MR imaging in the assessment of the AAR in patients with AMI.…”
Section: Area At Riskmentioning
confidence: 99%
“…18 In a subsequent study they reported on the correspondence between the 17-segment model and coronary artery anatomy with contrast-enhanced CMR imaging in 93 patients flowing AMI treated with primary PCI. 96 They found that four segments (2,7,8,and13) were 100% specific for LAD occlusion, while no segments were 100% specific for LCx or RCA occlusion.…”
Section: Correspondence Between Left Ventricular 17 Myocardial Segmenmentioning
confidence: 99%